Simultaneous study of the antioxidant activity, microbial decontamination and color of dried peppermint (Mentha piperita L.) using low pressure cold plasma. (April 2020) - Kashfi, Atefeh Sadat; Ramezan, Yousef; Khani, Mohammad Reza
Abstract: This study purpose was to investigate the effect of radiofrequency low pressure cold plasma (LPCP) process by using dried peppermint (Mentha piperita) on the reduction in microbial load, antioxidant activity, total phenolic content, and color. The microbial load of the sample was investigated by infecting it with 10 6 CFU/g of Escherichia coli O157:H7, and after treatment with LPCP at 20, 50, and 60 W for 20 min. It was found that LPCP process had a significant effect on the removal of E. coli O157:H7 at 50 and 60 W, but at 20 W revealed no significant effect on this bacterium removal ( p > 0.05). The LPCP significantly increased the total phenolic content ( p < 0.05); consequently, antioxidant activity increased after studying the antioxidant properties by two methods of FRAP and DPPH in all 3 powers. The results also indicated that the LPCP darkened the treated sample's color. Highlights: Dry peppermint was treated by RF low pressure cold plasma. Escherichia coli O157:H7 removed after treatment for 20 min at 50 and 60 W. 50 W significantly increased total phenolic content and antioxidant activity. Low pressure cold plasma significantly darkened the treated sample's color.